Pengaruh Penerapan Permainan Tradisional dalam Pembelajaran Terhadap Kemampuan Motorik Kasar Anak Tunagrahita di Sekolah Dasar Luar Biasa - BuluBaan, Addriana; Gunawan, Gunawan; Abduh, Ikhwan (Universitas Hamzanwadi, 2025)
Gross motor skills of children, especially children with special needs, are sometimes a problem that requires special intervention. In this study, treatment will be carried out on children with special needs by playing traditional games and then seeing the effect on children's gross motor skills. The sample involved was 30 children with special needs, the instrument used was the TGMD-2 instrument. The types of traditional games that will be carried out are the mongalas game, nobangan which is a game that is widely practiced in Central Sulawesi, besides that, the hadang game will be used as a form of treatment. Data analysis techniques that will be carried out are frequency distribution analysis and t test. The results showed that the value of the t test in the 3 schools where the research was conducted, namely at the ABC SLB school 4.154, Cahaya Nurani SLB 3.825 and SLBN 1 Palu 4.382 the overall significance value < α 0.05 so it can be concluded that the treatment of traditional games has an effect on improving the gross motoric abilities of students with special needs in the 3 schools where the research was conducted.